PENGARUH CAPITAL ADEQUACY RATIO DAN NET INTEREST MARGIN TERHADAP HARGA SAHAM PADA BANK KONVENSIONAL YANG TERDAFTAR DI BEI PERIODE 2019-2023 - Desy Fitriani; Novia Nour Halisa; M. Hasanur Arifin; Fitriyadi (Smart Business Journal (SBJ), 2025)
This research aims to identify and analyze the impact of the Capital Adequacy Ratio (CAR) on the stock prices of conventional banks listed on the Indonesia Stock Exchange (IDX) for the period from 2019 to 2023, focusing on partial effects. Additionally, the study seeks to evaluate the influence of Net Interest Margin (NIM) on the stock prices of conventional banks during the same time frame, again looking at partial effects. Another goal is to investigate the simultaneous effects of CAR and NIM on the stock prices of conventional banks listed on the IDX within the 2019-2023 period. This study employs a quantitative methodology featuring an explanatory research design. The population encompasses all financial statements from conventional banks listed on the IDX. The sample was selected through purposive sampling, resulting in 30 samples. Data collection utilized the documentation method, and the analysis was performed using multiple linear regression with SPSS software version 25.0. The findings indicated that the Capital Adequacy Ratio (CAR) had a significant partial effect on the stock prices of conventional banks listed on the IDX during the 2019-2023 period. Furthermore, the results demonstrate that the Net Interest Margin (NIM) also significantly affects the stock prices of conventional banks in the same period. Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) have a significant simultaneous effect on stock prices of Conventional Banks listed on the IDX for the period 2019-2023.